The Role of NGOs in Indonesia - Australia Cooperation Through the KOMPAK Program to Support the SDGs of Quality Education in Papua and West Papua - Satianingsih, Rarasaning; Erqie, Kirana Evan Salsabilla; Wardhani, Baiq L. S. W.; Rosmiati, Rosmiati; Satriawan, Muhammad; Sulistyowati, Ida (International Journal of Artificial Intelligence Research, 2024)
This paper discusses the role of Non-Governmental Organizations (NGOs) in bilateral cooperation between Indonesia and Australia through the KOMPAK program, with a focus on supporting the Sustainable Development Goals (SDGs) for quality education in Papua and West Papua. KOMPAK, which is supported by the Australian government, aims to improve the quality of life in Indonesia by strengthening basic services, including education. NGOs play an important role in implementing this program by leveraging local expertise to build capacity, increase access to education, and empower communities. This program is in line with the global commitment to SDG 4, which emphasizes inclusive and equitable quality education for all children, especially in remote and underserved areas. This collaboration shows the shared commitment between the two countries and highlights the important role of NGOs in improving the educational landscape in Papua and West Papua, with the aim of ensuring a better future for the region's young generation